Design and construction of a broadband Wilkinson Power Divider/Combiner - Guevarra, Rolando C.
Power dividers, directional couplers, and hybrid junctions are passive microwave components used for power division or power combining. Power dividers often are of the equal division (3 dB)type, but unequal power division ratios are also possible. This paper describes the design, construction and characterization of a low loss broadband Wilkinson power divider/combiner implemented in microstrip using low cost FR4 and metal film resistor. Major results include broadband DC-6 GHz frequency range, 0.0314 dB insertion loss above 3 dB, 38 dB isolation at the design frequency, 0.0 phase unbalance, 0.0334 dB amplitude unbalance and a 1.0694 : 1 VSWR.